Systematic integrated approach to quantifying preventive diagnostics in a "smart" transport system - Natallia Yankevich (Journal of Industrial Engineering International, 2019)
One of the main tasks facing all European countries for the next few years is the creation of the most dynamically organized transport sector. The constant passenger and freight traffic lead to congestions and pollutions at the transport highways, having negative impact on a person. Thus, introduction of new technologies, addressing the interrelated problems of optimizing transport flows and improving the environmental footprint of transport, is an overriding priority. In this respect, approaches that allow analyzing the reliability of a vehicle as an object characteristic, reflecting the ability of a product to operate without sudden changes in its quality in real time, are of considerable interest. This is reflected in the development of preventive diagnostic systems (warning the driver of a possible failure of the systems and the car as a whole). The concept for formation of normative and methodological support for research in the field of reliability of complex systems (including vehicles), which can be adopted as a basis for the development of a database of a preventive diagnostic system, is proposed.
Keywords: 650; ITS; Preventive diagnostics; Reliability; System approach